The effect of early age stunting on cognitive achievement among children in Vietnam - Duc, L (Young Lives, 2009)
In this paper, we use a longitudinal data set that follows three thousand children in Vietnam to study the economic significance of childhood poverty–cognitive achievement nexus. Focusing on the consequences of stunting, we look at height-for-age z-score (HAZ), and trace the impact of HAZ on child cognitive achievement independent of the source of HAZ’s variation - whether it comes from the variation in child characteristics at birth and the environmental factors, or in the household characteristics (stature, socioeconomic status, etc.). An increase by a standard deviation of HAZ at the age of one expectedly leads to an increase by one fourth of a standard deviation of the log score in a widely-used test of language ability at the age of five. For a quantitative cognitive achievement test, the corresponding figure is 0.20. Our evidence suggests that some of the disadvantages in socioeconomic status are being transmitted across generations.